Q-method as a tool to facilitate meaningful public engagement with science. (18th October 2019) - Gauttier, Stéphanie
Abstract : Purpose: Researchers are expected to find ways to make citizens participate in research to support responsible and open conceptions of science. New methods for engagement need to be found in order to facilitate engagement. The public needs to build its knowledge and be presented with time for reflexion so as to give an informed opinion on a given topic. Traditional consensus conferences are costly, and surveys are not building citizens' understanding of science. The paper aims to discuss these issues. Design/methodology/approach: The author presents a case where engagement was realized based on Q-method and technique. A research protocol and the results of the engagement are presented. Findings: This case shows that an adapted version of Q can lead to meaningful engagement for citizens and relevant data for researchers. Participants enjoy the process and can become advocates for a topic. The data collected allow to map out points of views which can be used to inform policy and research. Originality/value: From a practical point of view, this paper suggests a new way to proceed to citizen engagement with science. It also opens research questions related to the use of the method itself.